Joyce's Dante exile, memory, and community - Robinson, James A. (Cambridge University Press, 2016)
"Joyce's engagement with Dante is a crucial component of all of his work. This title reconsiders the responses to Dante in Joyce's work from A Portrait of the Artist as a Young Man to Finnegans Wake. It presents that encounter as an historically complex and contextually determined interaction reflecting the contested development of Dante's reputation, readership and textuality throughout the nineteenth century. This process produced a 'Dante with a difference', a uniquely creative and unorthodox construction of the poet which informed Joyce's lifelong engagement with such works as the Vita Nuova and the Commedia. Tracing the movement through Joyce's writing on exile as a mode of alienation and charting his growing interest in ideas of community, Joyce's Dante shows how awareness of his changing reading of Dante can alter our understanding of one of the Irish writer's lasting thematic preoccupations"...
Includes bibliographical references and index
Keywords: Joyce, James -- 1882-1941 -- Criticism and interpretation; Dante Alighieri -- 1265-1321 -- Influence; Joyce, James -- 1882-1941; Dante -- Alighieri -- 1265-1321; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Exiles in literature; Memory in literature; Community in literature; Erinnerung -- Motiv; Gemeinschaft -- Motiv; Rezeption; Exil -- Motiv